Punching bag with speed and accuracy gauge - Cacacho, R. R.; Oyas, F.; Priolo, J. P.; Yasis, G.; Dereje, W. (International Journal of Sports Science and Engineering, 2008)
This study reports on the design of a punching bag that has the capability to gauge a boxer`s accuracy and speed. It aims to help the user of this prototype to improve condition which concerns the speed of the punch and accuracy to hit a designated target. A graphical user interface (GUI) allows the user to select from several training modes or to select a pre-defined training sequence. Real-time output measurements are displayed by the GUI after every registered hit.